The Potency of Camellia Sinensis L. to Reduce Proinflammatory Cytokine Levels in the Acute Respiratory Distress Syndrome Rat Model - Wahyu Widowati; Didik Priyandoko; Hanna Sari Widya Kusuma; Rizal Rizal (Directorate for Research and Community Services (LPPM) ITB, 2023)
This study was conducted in order to ascertain how green tea extract (GTE) could affect inflammatory markers, including level of interleukin-(IL)-12, IL-18 of serum and lung, tumor necrosis factor (TNF)-α, gene expression of NLR family-pyrin-domain containing 3 (NLRP3) of lung, nuclear factor kappa B (NF-κB), lung histopathology, and IL-6 expression of lung tissue in lipopolysaccharide (LPS)-treated rats as ARDS animal model. Rats were given GTE at dosages of 0, 50, 400, 800 mg/kg of body weight for 28 days to boost their immune systems. The rats were then stimulated with LPS (5 g/kg of BW) and after that continued to receive GTE for 28 days. Levels of serum or lung IL-18, IL-12, TNF-α, were measured using the ELISA method; expression of lung NF-κB and NLRP3 was measured by qRT-PCR; immunohistochemistry (IHC) was implemented to assess lung IL-6 expression; and lung histopathology was evaluated through the bleeding, inflammation, and alveolus scores. GTE had the ability to lower serum IL-18, lung TNF-α, and lung IL-12 levels; suppress the lung gene expression of NF-κB, NLRP-3, IL-6 expression; and improve lung histopathology. Green tea extract inhibited inflammation in the ARDS rat model by decreasing the proinflammatory cytokine level and proinflammatory gene expression.